WORK SATISFACTION OF GENERAL NURSES - Vévoda, Jiří; Ivanová, Kateřina; Nakládalová, Marie; Marečková, Jana (Profese Online, 2010)
Aim: The aim of the thesis was to identify personal priorities of factors of general nurses' working environment and the level of their fulfilment by employer. Then, by mutual comparison, to present the most significant divergences between wish and reality of general nurses in their working environment. Creation of such tool, suitable for the purpose, which would be utilizable for fulfilment of accreditation standard discussing the monitoring of work satisfaction of employees in health service, was also an aim.Methods: In 2004, basic material for questionnaire investigation was created based on the Herzberg's double-factor motivation theory and after discussions with managers of hospitals. In 2005, pilot research was carried out. Verified questionnaire was sent to 25 hospitals during 2006; it was processed during 2007-2008. 3081 questionnaires out of 10 791 distributed questionnaires got to final processing.Results: Wage, care of patients and job stability are the top ranked positions on general nurses' personal list. Wages, job stability and appreciation of personal results were among the most diverging factors. The following factors were the most harmonious: relations to first line supervisors, provided social benefits and cooperation with other professions (factors are mentioned in sequence according to importance).Conclusions: The research team has created the questionnaire as a measurement tool by which effect of motivation interventions can be easily determined without redundant human and financial resources wasting. By the questionnaire, requirements of the Accreditation Standard focused on satisfaction of employees can be fulfilled and comparative investigation among individual hospitals can be carried out.
Keywords: motivation; work satisfaction; fluctuation; work contentment; hospital; general nurse; Herzberg's theory